Trajectory optimization of ultra-short sidetrack horizontal wells in marginal reservoirs - Jiang, Yanjiao; Zhou, Jian; Zhang, Jiaqi; Guo, Zhihua; Liu, Dan; Li, Xueying; Gao, Jinbiao (Frontiers in Earth Science, 2025)
The thin thickness of the sand body and the low oil recovery in the marginal reservoirs of the X area in D oilfield pose significant challenges. Using ultra-short radius horizontal wells is effective for substantially increasing production and designing reasonable well trajectory parameters is crucial for realizing the potential of oil reservoirs. Based on the actual geological system and the rock physical characteristics of the reservoir, and using the theory of oil-water two-phase seepage, a three-dimensional numerical simulation model is established for ultra-short horizontal wells in edge reservoirs to analyze the impact of horizontal well parameters on production. The simulation results show that the production increases with a longer horizontal section length, a greater entry distance, and larger angles between the well and mainstream flow line. The numerical results reveal that the optimal horizontal well length is 200 m, the optimal well orientation is 120°–150° to the main flow line, and the preferred range of entry distance is 50–70 m. For thin layers, horizontal wells located in the middle of the layer are optimal. Based on a coupled analysis of fluid flow in the horizontal wellbore and fluid seepage in the reservoir, a reasonable theoretical length of the horizontal well section is determined, and its reliability is verified with examples. The theoretical analysis is consistent with the simulation results. This study elucidates the influence of drilling trajectory parameters on thin-layer oil marginal reservoirs, and the determination of optimal parameters improves the scientific basis of trajectory design. These findings provide an important reference for residual oil dredging strategies.